THE INFLUENCE OF ORGANIZATIONAL CLIMATE AND ORGANIZATIONAL COMMITMENT ON EMPLOYEE PERFORMANCE AT PT SWAKARSA SAWIT RAYA INDRAGIRI HULU - Alisya Miranda; Seno Andri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
The company is one of the large and comprehensive forms of organization contained in it human beings who act as mobilizers to advance the company. This research uses this type of research with quantitative approach. As for the independent variables of this research, Organizational Climate (X1) and Organizational Commitment (X2). As for dependent variables in this research Employee Performance (Y). Sampling techniques using Simple Random Sampling method, then data collection techniques through questionnaires and interviews to employees of PT Swakarsa Sawit Raya Indargiri Hulu. Data processing uses simple linear regression analysis and multiple linear regression using SPSS 25.This study aims to determine the influence of organizational climate and organizational commitment on employee performance. The sample of this study was taken by 62 respondents. The results of this study showed that organizational climate affects employee performance. Organizational commitment affects employee performance. Organizational climate and organizational commitment affect employee performance. Keywords: Organizational Climate, Organizational Commitment, Employee Performance, PT Swakarsa Sawit Raya Indragiri Hulu